The whys of a Philosophical Scrivener. - "Gardner, Martin." (Oxford, 1985)
For 25 of his 95 years, Martin Gardner wrote 'Mathematical Games and Recreations', a monthly column for Scientific American magazine. These columns have inspired hundreds of thousands of readers to delve more deeply into the large world of mathematics. He has also made significant contributions to magic, philosophy, debunking pseudoscience, and children's literature. He has produced more than 60 books, including many best sellers, most of which are still in print. His Annotated Alice has sold more than a million copies. He continues to write a regular column for the Skeptical Inquirer magazine.
Keywords: Philosophy